FORMATION OF ICT COMPETENCES FUTURE TEACHER OF COMPUTER SCIENCE IN THE ELEMENTARY SCHOOL VIA DELPHI SYSTEM - Pustovit, Г.П.; Petrenko, С.В. (Journal of Information Technologies in Education (ITE), 2015)
In article, authors clarified the concept of "ICT competence of future teachers of computer science in the elementary school"; improved criteria for formation of the ICT competences future teachers of computer science in the elementary school to identify the system ready for use Delphi during process of visual programming in professional activity. We present the model of the formation of the ICT competence future teachers of computer science in the elementary school via visual programming tools, where importance given to the construction of individual learning paths, taking into account individual learning rhythm, because students have different levels of training, they are different in nature perception of information. It is proved that the proposed model will make it possible to carry out training, starting from the result of the educational process at the university, which takes into account the impact of external and internal variables, as well as a feedback mechanism that allows adjustment of the process at different stages. Authors presented developed method of forming ICT competences future teachers of computer science in the elementary school via Delphi tools during learning of visual programming,feature of which is that to present course materials were chosen LMS Moodle platform.